Desorganización familiar y el desarrollo afectivo en los adolescentes de la Unidad Educativa Cmdt. Rafael Moran Valverde, año 2018 - Naranjo Noblecilla, Luisana Luandi (2019)
The family is the basis of society, an organized family promotes an integral development in the adolescent, it can be said that the family is vital within each home so that it can have greater emotional control, the form of appropriate service with their parents, have interpersonal relationships, among other skills, which does not occur in the case where the adolescent has grown up in a family disorganization. The term "family disorganization" refers to the dispersion or disintegration of one of the parents within the home, partial or partial. Within the analysis of affective development and its influence on adolescents, we have the same incentive, communication, conflicts, control and the promotion of autonomy. The empirical literature already exists on this subject indicates that adolescents are very favored when we have parents who are affectionate, communicative and encourage them to be autonomous. Due to the imbalance in which adolescents are found, family disorganization tends towards a better balance in their emotional state and school performance, which implies that they can not count on a favorable family climate that provides them with security, Stability, support and guidance that guides you in the best way in the stage of your adolescence.